Effects of Heat-Moisture Exchangers and Dead Space Compensation on CO2 Clearance and Mechanical Power in Critically Ill Intubated Subjects. - Dorado, Javier H.; Perez, Joaquín; Steinberg, Damián; Plotnikow, Gustavo A.; Bertozzi, Matías; Accoce, Matías (Respiratory Care, 2026)
Background: Heat and moisture exchangers (HMEs) preserve airway humidification in mechanically ventilated subjects. However, the additional instrumental dead-space (VD) may impair carbon dioxide (CO2) elimination and require an increase mechanical power (MP), both associated with higher risk of ventilator-induced lung injury. The physiological effects (PaCO2 and MP) of HME use and instrumental VD compensation strategies have not been comprehensively evaluated. We sought to evaluate the impact of HMEs on arterial CO2 and MP in intubated subjects undergoing controlled mechanical ventilation, and to compare the effect of compensation strategies—tidal volume (VT) or breathing frequency (f)—on CO2 and MP. Methods: Prospective crossover study including intubated adults receiving controlled mechanical ventilation. We evaluated 4 conditions. (1) HME, (2) no HME, (3) HME + high VT, (4) HME + high f. Main outcomes were PaCO2 and MP. Results: Adding the HME increased PaCO2 and ventilatory ratio and reduced arterial pH (P <.001). When VT or f was increased to compensate for the HME-associated VD, the PaCO2 decreased (P <.001) but the MP increased (P <.001), mainly because of its resistive component. A compensation strategy based on higher VT was more effective in restoring PaCO2 to baseline levels than increasing f (P =.035); however, increasing VT augmented the global and elastic MP (P <.001 and P =.002, respectively). Conclusions: The HME impaired CO2 elimination. Increasing VT or f to compensate for the HME-associated VD increased MP. At an equivalent minute ventilation, increasing VT was more effective for CO2 clearance but may compromise lung protection. Under iso-CO2 conditions, the strategies did not differ.